Financial Ratio-Based Corporate Bankruptcy Prediction to Reduce Investment Loss Risk - Nurbaiti; Iwan Hermawan; Alvianita Gunawan Putri (Research Synergy Foundation, 2025)
The increasing risk of bankruptcy that occurs in the textile industry today is a result of macroeconomic pressures, such as decreased demand and inflation, which has resulted in 7 textile companies closing and 8 companies making efficiency. The intent of this study is to investigate the effect of financial ratios such as profitability ratios, operational ratios, and liquidity ratios on the level of financial distress as measured by the Grover model (G-Score), as well as to develop a financial ratio-based risk prediction model. The study methodology employs a positivist perspective, a quantitative approach, secondary data, and a purposive sampling procedure. The data were analyzed using the IBM SPSS 26 tool, which included descriptive statistical tests, classical assumptions, multiple regression, and hypothesis testing. The profitability ratio, operational ratio, and liquidity ratio were found to have a 79.5% influence on the extent of financial distress. Each ratio has a substantial impact on the level of financial difficulty. This study adds theoretically to signaling theory regarding the financial ratios as indications of bankruptcy risk. Practically, this model can be an early detection tool for bankruptcy risk, assist in the preparation of risk mitigation strategies, and increase investment attractiveness in the Indonesian textile industry. Keywords financial distress, liquidity ratio, operational ratio, profitability ratio, signal theory